Effect of Ultrasonic Nanocrystalline Surface Modification (UNSM) on Stress Corrosion Cracking of 304L Stainless Steel - Hyunhak Cho; Young-Ran Yoo; Young-Sik Kim (Metals)
The nuclear industry uses 304L stainless steel to construct canisters for storing spent nuclear fuel. The spent nuclear fuel canisters require the lifetime prediction and robustness of their corrosion behavior over periods ranging from thousands to hundreds of thousands of years. Since nuclear power plants are predominantly located in coastal areas, where storage conditions are highly vulnerable to chloride environments, extensive research has been conducted to enhance the canisters’ stress corrosion cracking (SCC) resistance. The welded canisters inherently possess residual tensile stress, prompting the application of plastic deformation-based techniques to boost their SCC resistance, with peening being the most prevalent method. It is reported that UNSM increases the SCC resistance by plastic deformation through surface treatment. In this study, the commercial 304L stainless steel was subjected to UNSM treatment on base metal, heat affected zone (HAZ), and weld metal U-bend test specimens to induce compressive residual stresses up to a depth of 1 mm. The impact of peening treatment on SCC properties was explored through microstructural analysis, corrosion properties analysis, and compressive residual stress assessments. The U-bend specimens underwent SCC testing (in 42% MgCl2 at 155 °C), microstructure examination using an optical microscope (OM) and a scanning electron microscope (SEM), electron backscatter diffraction (EBSD) analysis, and compressive residual stress measurements via the hole-drilling method. Corrosion behavior on the surface and cross-section was evaluated using anodic polarization tests, electrochemical impedance spectroscopy (EIS) measurements, double loop-electrochemical potentiokinetic reactivation (DL-EPR) tests, and ASTM A262 Pr. C tests. The compressive residual stress imparted by UNSM refined the outermost grains of the cross-section and enhanced the corrosion resistance of 304L stainless steel. Furthermore, it led to a longer crack initiation time, a reduced crack propagation rate, and improved SCC properties.